2023
DOI: 10.1021/acs.jpcc.3c05409
|View full text |Cite
|
Sign up to set email alerts
|

Infrared and Raman Diagnostic Modeling of Phosphate Adsorption on Ceria Nanoparticles

Khoa Minh Ta,
David J. Cooke,
Lisa J. Gillie
et al.

Abstract: Cerium dioxide (CeO2; ceria) nanoparticles (CeNPs) are promising nanozymes that show a variety of biological activity. Effective nanozymes need to retain their activity in the face of surface speciation in biological environments, and characterizing surface speciation is therefore critical to understanding and controlling the therapeutic capabilities of CeNPs. In particular, adsorbed phosphates can impact the enzymatic activity exploited to convert phosphate prodrugs into therapeutics in vivo and also define t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…2B) is in good agreement with the similar GGA+U calculations of Zhou et al 79 However, we predict a different {100}R-CO 2 -A configuration, which we attribute to a different configuration of the {100} flexible surface oxygen layer. 2,80,81…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2B) is in good agreement with the similar GGA+U calculations of Zhou et al 79 However, we predict a different {100}R-CO 2 -A configuration, which we attribute to a different configuration of the {100} flexible surface oxygen layer. 2,80,81…”
Section: Resultsmentioning
confidence: 99%
“…2B) is in good agreement with the similar GGA+U calculations of Zhou et al 79 However, we predict a different {100}R-CO 2 -A configuration, which we attribute to a different configuration of the {100} flexible surface oxygen layer. 2,80,81 XPS measurements by Yang et al 82 indicated that CO 2 adsorbs to the {110} surface as {110}S-CO 2 -A, {110}R-CO 2 -A, {110}S-CO 2 -M or {110}R-CO 2 -M, but were unable to determine geometries. We can therefore only compare our {110} configurations to other DFT studies.…”
Section: Structure and Energetics Of Co 2 Adsorptionmentioning
confidence: 99%